Gestión del Talento Humano para reducir el Síndrome de Burnout en el personal de enfermería - Narváez Lavanda, Milena Nicole (My University, 2025)
Burnout syndrome is a condition that significantly affects healthcare personnel, generating emotional exhaustion, depersonalization, and low personal accomplishment, which negatively impacts their well-being and the quality of service. Objective: To evaluate talent management in reducing the professional burnout syndrome of nursing staff at the San Vicente de Paúl Basic Hospital in the Pasaje canton, El Oro province. Method: The study used a quantitative, descriptive, and cross-sectional approach. Two instruments were applied: the Maslach Burnout Inventory (MBI) questionnaire to measure burnout levels, and a validated Likert scale questionnaire to assess perceptions of human talent management in areas such as recruitment, training, work environment, performance evaluation, and staff retention. Results: The data obtained from the surveys show that, although some areas such as recruitment and workplace climate were positively rated, weaknesses in continuous training and performance evaluation are evident. Regarding burnout syndrome, 43.4% of the staff reported medium or high levels of emotional exhaustion, 37.7% showed moderate or high depersonalization, and 41.5% expressed low personal accomplishment. Thus, the Spearman statistical analysis did not show a significant correlation between human talent management practices and the reduction of burnout. Conclusion: In this study, the perception of human talent management does not constitute a determining factor in levels of professional burnout, but from a theoretical perspective, proper management can act as a protective agent against professional wear and tear, improving resilience, motivation, and the quality of service. Recommendation: Strengthen continuous training programs, establish more objective performance evaluations, implement measures for emotional well-being, and promote empathetic leadership styles in order to reduce the prevalence of burnout and improve the organizational climate.
El síndrome de burnout es una condición que afecta significativamente al personal de salud, generando agotamiento emocional, despersonalización y baja realización personal, lo cual repercute negativamente en su bienestar y en la calidad del servicio. Objetivo: Evaluar la gestión del talento en la reducción del síndrome de burnout profesional de Enfermería del Hospital Básico San Vicente de Paúl, cantón Pasaje, provincia de El Oro. Método: El estudio empleó un enfoque cuantitativo, descriptivo y transversal. Se aplicaron dos instrumentos: el cuestionario Maslach Burnout Inventory (MBI), para medir los niveles de burnout, y se diseñó un cuestionario con escala tipo Likert validada, para evaluar las percepciones sobre la gestión del talento humano en dimensiones como reclutamiento, capacitación, clima laboral, evaluación del desempeño y retención del personal. Resultados: Los datos obtenidos de las encuestas muestran que, aunque algunas áreas como el reclutamiento y el clima laboral fueron valoradas positivamente, se evidencian debilidades en la capacitación continua y la evaluación del desempeño. En cuanto al síndrome de burnout el 43,4% del personal reportó niveles medios o altos de cansancio emocional, el 37,7% mostró despersonalización moderada o alta, y un 41,5% manifestó baja realización personal. El análisis estadístico de Spearman no evidenció una correlación significativa entre las prácticas de gestión del talento humano y la reducción del burnout. Conclusión: En este estudio la percepción sobre la gestión del talento humano no constituye un factor determinante en los niveles de agotamiento profesional, pero desde una perspectiva teórica una gestión adecuada puede actuar como agente protector frente al desgaste profesional, mejorando la resiliencia, motivación y la calidad del servicio. Recomendación: Fortalecer los programas de formación continua, establecer evaluaciones de desempeño más objetivas, implementar medidas de bienestar emocional y promover estilos de liderazgo empático, con el fin de reducir la prevalencia del burnout y mejorar el clima organizacional.
Keywords: GESTIÓN DEL TALENTO HUMANO; SÍNDROME DE BURNOUT; ENFERMERÍA; CLIMA LABORAL